Gestión universitaria de la innovación social promovida desde espacios académicos relacionados con el emprendimiento, la investigación y la proyección social - Jurado-Paz, Irina Margarita; Morán-Vallejo, Michael Alexander (Revista de Investigación, Desarrollo e Innovación, 2019)
This article shows the diagnosis of the Interdisciplinary Rural Internship Program, PIRI, held in a university institution in order to identify elements to improve its implementation. The research is descriptive, with a mixed approach, where surveys and interviews were used to collect information. A sample of 214 students was considered, belonging to different programs of the Autonomous University Corporation of Nariño. The results indicate significant contributions from PIRI to the institutions and to the students who have participated in the program. PIRI is used in an educational space for students to develop skills and apply their knowledge on issues related to social innovation. However, there are also difficulties such as the low number of participants, together with the lack of clear procedures that allow an adequate articulation of the entities linked to PIRI. In this sense, a model was formulated to facilitate the university management of social innovation in the institution under study, which articulates the dependencies of entrepreneurship, research and social projection, so that the benefits are oriented both to the university community and to the territories.
Number: 2
Keywords: Amérique latine; Colombie; Innovation sociale; Libre accès; Rôle des universités